Cronkhite–Canada syndrome: from clinical features to treatment. (4th October 2020) - Wu, Ze-Yu; Sang, Li-Xuan; Chang, Bing
Abstract: Cronkhite–Canada syndrome (CCS) is a rare acquired polyposis with unknown etiology. To date, >500 cases have been reported worldwide. CCS is typically characterized by gastrointestinal symptoms, such as diarrhea and skin changes (e.g. alopecia, pigmentation, and nail atrophy). Endoscopic features include diffuse polyps throughout the entire gastrointestinal tract, except for the esophagus. Pathological types of polyps in CCS mainly include inflammatory, hyperplastic, hamartomatous, and adenomatous polyps. CCS can be complicated by many diseases and has a canceration tendency with a high mortality rate. Moreover, there is no uniform standard treatment for CCS. A review of the reported cases of CCS is presented herein, with the goal of improving our understanding of this disease.